Synthesis and photophysical characterization of novel ESIPT triazinyl-benzazole derivatives - Barreto, Fabiano (2015)
In this work, the synthesis, characterization and photophysical study of new derivatives of triazinyl-benzazoles with fluorescence by excited-state intramolecular proton transfer (ESIPT) are presented. It regards the synthesis of cyanuric chloride with different 2-(2’-hydroxyphenyl) benzazoles, two quite attractive groups from the synthetic and technological point of view. These new compounds have several potential applications such as biological markers and new photoluminescent materials. The derivatives were characterized by 1H and 13C nuclear magnetic resonance (NMR), Fourier transform infrared spectroscopy (FTIR), high-resolution mass spectrometry (HRMS), UV-Vis absorption and fluorescence emission. The dyes are fluorescent by an excited-state ESIPT in the blue-orange region, with a large Stokes’ shift.